The Development of Banking Services and their Role In Enhancing the Volume of Credit Granted to The Private Sector in Iraq for the Period (2017-2022( - Lafta Mohammed*, Anwar; Kadhin Shamkhi, Mohammed (Journal of Economics and Administrative Sciences, 2024)
The advanced banking system serves as a vital cornerstone for economic growth due to the crucial services it provides to the economy. These services include mobilizing local savings through deposits, providing loans, monitoring project owners who borrow from banks, risk management, facilitating financial transactions, and more. The researcher utilizes banking service indicators (such as the ATM and POS penetration) and indicators of private sector credit (like the ratio of private sector credit to Gross Domestic Product) to examine the relationship between banking services and the volume of credit provided to the private sector in Iraq. The study aims to understand the evolution of banking services and their role in enhancing private-sector credit in Iraq. The study reveals that technological advancements, including the proliferation of ATMs, the facilitation of electronic withdrawal and deposit operations, and training bank employees in the use of communication and computer technology through research and development centers, are vital in keeping up with the transformations and developments in the modern banking industry. Paper: Research paper